Desenvolvimento de controlador para dosador de sementes eletropneumático - Kuhn, Leandro Klasener (2017)
Precision agriculture (AP) seeks alternatives to higher productivity. Precision Seeding (SP) is one of those that seems to be so simple to make but a bit difficult to put into practice, for a variety of reasons, a short planting window, an inadequate working speed and seed dispensers not qualified to achieve good dosage, with adequate equidistance and singularity. In the present work the objective was to develop a Controller for Seed Dosers of Electro-pneumatic Seeds controlled by an Arduino, some electronic components and a tablet for display function, where the information is presented. The choice for the Android system is made for its great potential in applications, a demand that becomes more effective every day. As for the Arduino, for its ease made available to the electronic medium, where you do not have to be an expert in electronics. To enter the market it is necessary to develop a controller with affordable price, with quality and ease of use, seeking to link this technology to the knowledge of the farmer, since this is the great success of Precision Agriculture (AP), working together between technologies of (AP) is the management of the information generated by the Farmer. Initially this controller will be responsible for managing the displacement of stepper motors, turbine (vacuum) drive and seed monitoring, the latter present in almost 100% of the active planters, produced by several brands whether these are Brazilian or from abroad , a necessary system, however, with a high cost for small farmers. And as a focus was mainly on small farmers, the challenge was to provide a system that would meet the expectations of large farmers at an affordable price for the small ones so that it is possible not only to produce a new system for the market, by the knowledge of those who understand farming can yield good results in the near future. All this dedication has resulted in a sophisticated controller with affordable price, to make (AP) affordable for Family Farming.